PyTHang: an Open-s-Source Wearable Sensor System for Real-Time Monitoring of Head-Torso Angle for Ambulatory Application - GÜRKAN, GÜRAY (Taylor & Francis Ltd., 2021)
This article presents the realization of a low-cost wearable sensor system and its Python-based software that can measure and record relative head-torso angle, especially in sagittal plane. The system is mainly developed to track head-torso angle during walk in a clinical study. The open-hardware part of the system is composed of a pair of triaxial digital accelerometers, a microprocessor, a Bluetooth module and a rechargeable battery unit. The reception of the transmitted acceleration data, visualization, interactive sensor alignment, angle estimation and data-logging are realized by the developed open-source graphical user interface. The system is tested on a tripod for verification and on a subject for practical demonstration. Developed system can be constructed and used for ambulatory monitoring and analysis of relative head-torso angle. Open-source user interface can be downloaded and developed for further (different) algorithms and device hardware.
Keywords: Accelerometer; Head-torso Angle; Wearable Devices; Open-hardware; Opensource Software